THE EFFECT OF PMA, PMDN AND MANPOWER ON PDRB OF EAST KALIMANTAN PROVINCE - Adi, Hanani Aprilia; Dewi, Retno Mustika (Perpustakaan dan Penerbitan Unismuh Makassar, 2020)
The purpose of this study was to determine the effect of Foreign Direct Investment (FDI), Domestic investment (DCI), and labor on Gross Regional Domestic Product (GRDP) in East Kalimantan Province in 2009-2018. This study uses the Ordinary Least Square (OLS) method. The results showed that the variable FDI had no significant effect on the GRDP of East Kalimantan Province with a coefficient value of 0.864 because the probability value was > 0.05%. When FDI has increased, the GRDP in East Kalimantan Province will experience a decline. While the DCI variable has no significant effect on the GRDP of East Kalimantan Province with a coefficient value of 0.395 because the probability value was > 0.05%. When DCI has increased, the GRDP in East Kalimantan Province will experience a decline. In addition, the labor variable has a significant influence on the GRDP of East Kalimantan Province with a coefficient value of 0.022 because the probability value was < 0.05%. When labor has increased, the GRDP in East Kalimantan Province will experience an increase.